Residual stress analysis in shot peened and fretting fatigued samples by the eigenstrain method - Korsunsky, A; Kim, K; Golshan, M; Regino, G (Trans Tech Publications, 2006)
Residual stresses in titanium alloy samples that were subjected to shot peening followed by fretting fatigue loading were investigated using a combined experimental and numerical analysis procedure based on the concept of eigenstrain. Fretting fatigue loading was carried out in hte pad-on-flat geometry using the Oxford in-line fretting rig. Flat-and-rounded pad shape was used to introduce the contact tractions and internal stress fields typical of the target application in aeroengine design. The specimens were in the shape of bars of 10 mm square cross-section shot-peened on all sides. Both the pads and specimens were made from the Ti-6Al-4V alloy. Small remote displacement characteristic of fretting fatigue conditions was applied in the experiments. The residal elastic strains in the middle of the pad-to-sample contact and near the rounded pad edge were measured using synchrotron X-ray diffraction on Station 16.3 at SRS Daresbury. A combination of finite element analysis and the distributed eigenstrain method was used in the simulations. Commercial finite element analysis software, ABAQus ver 6.41, was used to build the finite element model and to introduce the residual stresses into the model using eigenstrain distributions via a user-defined subroutine. In an unfretted shot peened sample an excellent agreement of residual stress profiles was obtained between the experimental data and model prediction by the variational eigenstrain procedure. In a fretted sample the residual stress change due to fretting was observed, and predicted numerically. A good correlation was found between the FE simulation prediction and the experimental data measured at contact edges.